Difficulties in Writing Recount Text Faced by Senior High School Students in Indonesia - Nanda Aprila Sinta; Yuli Astutik (International Consortium of Education and Culture Research Studies, 2019)
Writing an English for EFL learner is a difficult skill because English is a foreign language. Besides that, sometimes EFL learner is confused with organizing the idea, translating the language from Indonesia to English, follow the grammatical rule, find and write the proper vocabulary. In this research focus on the students' writing difficulties in recount text, the factors which influence the students' writing difficulties in recount text, and the way of the teacher solve the students' writing difficulties. This study investigates the writing difficulties of students in SMA Kemala Bhayangkari 3 Porong. In this study, the data served as a qualitative descriptive which took the students' exercise of recount text and interviewed the subject. The result shows that there are different difficulties for each students' ability. Internal and external factors also turned out to be one of the causes of difficulties faced by students in writing recount text. The results of interviews with teachers are known that teacher’s have used metacognitive strategies as solving problems faced by students in writing skills.